Patterns of Immune Infiltration in Endometriosis and Their Relationship to r-AFS Stages - Zhong, Qiyu; Yang, Fan; Chen, Xiaochuan; Li, Jinbo; Zhong, Cailing; Chen, Shuqin (Frontiers in Genetics, 2021)
Background: Endometriosis (EMS) is an estrogen-dependent disease in which endometrial glands and stroma arise outside the uterus. Current studies have suggested that the number and function of immune cells are abnormal in the abdominal fluid and ectopic lesion tissues of patients with EMS. The developed CIBERSORT method allows immune cell profiling by the deconvolution of gene expression microarray data. Methods: By applying CIBERSORT, we assessed the relative proportions of immune cells in 68 normal endometrial tissues (NO), 112 eutopic endometrial tissues (EU) and 24 ectopic endometrial tissues (EC). The obtained immune cell profiles provided enumeration and activation status of 22 immune cell subtypes. We obtained associations between the immune cell environment and EMS r-AFS stages. Macrophages were evaluated by immunohistochemistry (IHC) in 60 patients with ovarian endometriomas. Results: Total natural killer (NK) cells were significantly decreased in EC, while plasma cells and resting CD4 memory T cells were increased in EC. Total macrophages in EC were significantly increased compared to those of EU and NO, and M2 macrophages were the primary macrophages in EC. Compared to those of EC from patients with r-AFS stage Ⅰ ~ Ⅱ, M2 macrophages in EC from patients with stage Ⅲ ~ Ⅳ stage were significantly increased. IHC experiments showed that total macrophages were increased in EC, with M2 macrophages being the primary subtype. Conclusions: Our data demonstrate that deconvolution of gene expression data by CIBERSORT provides valuable information about immune cell composition in EMS.